2021
DOI: 10.1017/beq.2021.32
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics at Work: Convergence of Epidemiology and Ethics

Abstract: Like COVID-19, new infectious disease outbreaks emerge almost annually, and studies predict that this trend will continue due to a variety of factors, including an aging population, ease of travel, and globalization of the economy. In response to episodic public health crises, governments and organizations develop, implement, and enforce policies, procedures, protocols, and programs. The epidemiological triad is both a model of disease causation and fundamentally used to design and deploy such control measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Prior studies have also used combinations of foundations to increase messaging efficacy (Wolsko, 2017 ). This is one of the least restrictive means of improving the uptake of such policy, which has been put forward as a guiding ethical principle in designing policy pertaining to vaccine passports (Thornton et al, 2022 ). Policy communicators should note, however, that studies examining the effect of the vaccine passport on vaccination attitudes have found null results (de Figueiredo et al, 2021 ; Sotis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have also used combinations of foundations to increase messaging efficacy (Wolsko, 2017 ). This is one of the least restrictive means of improving the uptake of such policy, which has been put forward as a guiding ethical principle in designing policy pertaining to vaccine passports (Thornton et al, 2022 ). Policy communicators should note, however, that studies examining the effect of the vaccine passport on vaccination attitudes have found null results (de Figueiredo et al, 2021 ; Sotis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…MFT is, therefore, highly applicable to issues that have both moral and political considerations, such as the COVID-19 vaccination (Albrecht, 2022 ; Sharfstein et al, 2021 ) or vaccine passports (The Economist, 2021 ). Furthermore, due to the centrality of the liberty foundation to ethical debates (Thornton et al, 2022 ) about vaccine passports (Grossin et al, 2021 ), we also examined the impact of the liberty foundation in this study.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The epidemiological triangle model is a crucial tool for developing and implementing such preventive interventions as well as a model of illness causation. The epidemiological triangle model's main objectives are to better understand how a disease spreads, identify the factors that led to disease transmission, and provide guidance for choosing an efficient disease control strategy [9] [10].…”
Section: Introductionmentioning
confidence: 99%